SOCIAL PHOBIA - Prabu Supramaniam (Universitas Udayana, 2013)
Social Phobia is a condition characterized by a marked and persistent fear of social or performance situations in which embarrassment may occur. Exposure to the social or performance situation almost invariably provokes an immediate anxiety response. Although adolescents and adults with this disorder recognize that their fear is excessive or unreasonable, this may not be the case in children. Most often, the social or performance situation is avoided, although it is sometimes endured with dread. In individuals younger than 18, symptoms must have persisted for at least 6 months before is disorder is diagnosed. This diagnosis should not be given if the fear is reasonable given the context of the stimuli (e.g., fear of being called on in class when unprepared). The disturbance must cause clinically significant distress or impairment in social, occupational, or other important areas of functioning. This disorder is not due to a medical condition, medication, or abused substance. It is not better accounted for by another mental disorder.